An evaluation of predicting corporate bankruptcy model by using MDA and logistic regression methods: Evidence from the UK service industry - Cai, Jing (2018)
While the world economy is slowly recovering, there are still many uncertainties in the economic environment. One such uncertainty is that the SMEs are facing more severe pressure and challenges; For SMEs it is important that any potential bankruptcy be recognized at the earliest opportunity. The Altman Z-score model is one of the most well-known default prediction models by using MDA method. However the performance of the Altman Z-score model is often found to be unsatisfactory due the changes in time and the original limitations of the model. This study uses United Kingdom's SMEs as a sample group and MDA and logistics modeling methodology. A bankruptcy prediction model is employed to find the best way to predict default risk in UK. It combines nine financial variables, covering a firm's financial information of operation, profitability and solvency. The empirical results show that the UK-based MDA model and logistics model has better predicting ability than the original Altman Z''-score model in the UK SMEs group. Additionally, the logistic regression model has the highest accuracy rate in this study.